Analysis and evaluation of albergo diffuso as sustainable business model: Case study of ‘Ražnjevića dvori’ - Hrvatin, Stella; Markuz, Ana; Miklošević, Ivana (Oeconomica Jadertina, 2022)
Social entrepreneurship literature continuously emphasizes the need for innovations in business models as businesses gain more importance in achievement of sustainable development. However, there is a lack of practical examples of sustainable business models which prevents their faster adoption among entrepreneurs. This paper analyzes and evaluates alternative hospitality model - Albergo diffuso which is by many authors considered to be an example of sustainable business model. Albergo diffuso is used for tourism restart and revitalization of rural areas as it recovers old buildings, creates new jobs, involves local farmers and entrepreneurs in value creation network and preserves local traditions. This paper applied qualitative research approach to analyze the business model of Croatian Albergo diffuso ‘Ražnjevića dvori’ using the semi-structured interviews. Tourism is of huge importance for economies around the world but at the same time it produces a lot of negative environmental and social impacts on local communities. Therefore, sustainable innovation, especially in business models, is needed to achieve sustainable development of tourism. This research showed that Albergo diffuso can be regarded as a sustainable business model because it creates sustainable value, includes stakeholders in the value network and establishes mutual value flows and thirdly internalizes negative environmental and social externalities. Researchers conclude that with small adjustments, Albergo diffuso as sustainable business model could contribute to sustainable tourism development. However, conclusions cannot be generalized due to limitations of the study that include small research sample and application on single case and further research is required.